2022
DOI: 10.3389/fonc.2022.893206
|View full text |Cite
|
Sign up to set email alerts
|

The Cellular and Molecular Landscape of Synchronous Pediatric Sialoblastoma and Hepatoblastoma

Abstract: Sialoblastoma (SBL) is an infrequent embryonal malignant tumor originating from the salivary gland, resembling primitive salivary gland anlage, whereas hepatoblastoma (HB) is the most common pediatric liver malignancy. The simultaneous occurrence of both tumors is extremely rare. Here we reported a case of a 6-month-old infant diagnosed with synchronous SBL and HB. The patient received neoadjuvant chemotherapy followed by surgical resection. Fresh tissues of both tumors were collected before and after chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In the screening phase, 103 articles were selected for full‐text evaluation. Of these, 51 selected studies 3,5,7–10,13–57 met the eligibility criteria. Additionally, 1 article 58 was added from a manual search of the reference lists of included studies, resulting in the inclusion of 52 articles in the qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the screening phase, 103 articles were selected for full‐text evaluation. Of these, 51 selected studies 3,5,7–10,13–57 met the eligibility criteria. Additionally, 1 article 58 was added from a manual search of the reference lists of included studies, resulting in the inclusion of 52 articles in the qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In one case the sex was not reported. 50 Anatomical location was reported in all included cases. Most of the lesions affected the parotid gland (n = 28; 45.2%), followed by the submandibular gland (n = 18; 29.0%) (Figure 2).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been at least eight reported cases of synchronous sialoblastoma and hepatoblastoma. The analysis of one such case conducted by Yang et al [ 26 ] revealed that certain germline mutations might be associated with the development of such a bizarre combination. Since few cases of sialoblastoma have been reported to date, the combination of sialoblastoma cases with co-existing hepatoblastoma is significant, and every patient with sialoblastoma should be carefully assessed for a possible abdominal tumor with proper abdominal imaging and AFP level measurement (sialoblastoma itself can also generate elevated AFP levels) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike immature teratoma, both carcinosarcoma and undifferentiated carcinoma of liver do not contain mature epithelial or mesenchymal components such as squamous epithelium, mature cartilage or adipose tissue [ 26 ]. Hepatoblastoma occurs mainly in children but rarely in adults, consisting of variable combinations of epithelial and mesenchymal elements, which are absent in this case [ 27 ].…”
Section: Discussionmentioning
confidence: 99%